Transport of pollutants from Pilliga Forest wildfires in northern New South Wales in December 2023 and its impact on air quality - Duc Hiep Nguyen; Watts Sean; Kong Jing; Azzi Merched; White Stephen; Tam Eugene; Chang Lisa Tzu-Chi; Monk Khalia; Fuchs David; Firth Justine; Trieu Toan; Jiang Ningbo (E3S Web of Conferences)
In mid-December 2023, a large wildfire occurred in Pilliga Forest, Duck Creek, about 20 km south of the town of Narrabri in northern New South Wales. The fire was started and caused by lightning. It quickly spread due to high temperature at the start of the austral summer. At the end of the fire, totally about 130,000 ha of forest and bushland were burned. Even though it was not large compared to the Black Summer megafires 4 years ago in 2019 which was also started in northern New South Wales near the coast, but this Pilliga Forest wildfire had a widespread impact on air quality over a number of towns and cities in the central and coastal New South Wales areas including the Hunter regions and metropolitan area of Sydney. Of interest is the fast transport of the smoke plumes in the upper troposphere southward inducing pyrocumulonimbus clouds formation and causing thunderstorms along the plume transport path and the intrusion of smoke plumes to the ground over the upper and lower Hunter and the Sydney metropolitan areas causing high particle episodes. The air quality model WRF-Chem (V4.4.2) is used in this study to analyse the dispersion and transport of air pollutants from the fire emission at Pilliga. The model results give insights on the vertical structure of transported plumes which is also compared and validated with aerosol profiles from ceilometer data at Merriwa, the global MERRA reanalysis data and CALIPSO satellite. Wildfires in remote forest areas by its nature are spontaneous but they can cause widespread effect on air quality in populated areas far from the fire sources. Lessons on the future preparation of these types of wildfires with respect to air quality forecasting in the metropolitan areas will be discussed.